Factors influencing inpatients perception of psychiatric hospitals: A meta-review of the literature. (April 2021) - Modini, Matthew; Burton, Amy; Abbott, Maree J.
Abstract: Inpatient psychiatric hospitals have remained a standard aspect of mental health treatment for many centuries. While numerous treatments have been empirically validated to assist inpatients, less is known about how inpatients perceive psychiatric hospitals. A meta-review, which is a systematic review of systematic reviews, was conducted to examine the factors reported by inpatients which affect their perception of psychiatric hospitals. MEDLINE, PsycINFO and EMBASE were systematically searched. Reviews that considered the perception of adults with mental illness admitted to an inpatient psychiatric hospital were eligible for inclusion. The AMSTAR-2 was used to assess for methodological quality and bias of eligible reviews, with reviews judged to have critical issues excluded. Thematic synthesis was used to detect key overarching factors that generalised across multiple reviews. Twelve systematic reviews were included of which seven key factors were extracted. These were; relationships on the ward, the ward environment, coercive measures, legal status, autonomy, feeling deserving of care, and expectations of care at admission and discharge. Inpatients report several factors that need to be considered when creating a therapeutic environment in a psychiatric hospital. While the importance of therapeutic rapport was the most consistently referenced factor in the included reviews, all factors are likely interwoven and modifiable. Limitations of this meta-review and directions for future research are discussed.